Synthesis and characterization of activated carbon from natural asphaltites - Tsyntsarski, B.; Marinov, S.; Budinova, T.; Yardim, M. Ferhat; Petrov, N. (Elsevier BV, 2013)
Abstract A possibility for utilization of natural asphaltites, based on production of carbon adsorbents, was investigated. Various combinations of physical and chemical activation as well as demineralization procedures were used to obtain final products from natural asphaltites. Carbon adsorbents with developed pore structure and with alkaline character of the surface, as well as tar and gas products, were obtained by water vapor pyrolysis of natural asphaltites. The obtained carbon adsorbents show good adsorption properties; however, this performance is somewhat limited, probably due to their high mineral and sulfur content. It was established that hydropyrolysis is not appropriate method for production of carbon adsorbents on the base of asphaltites from Sirnak deposit due to the material coking. However, a two-stage process, including carbonization and subsequent activation, is appropriate for obtaining of carbon adsorbent with developed pore structure from Sirnak asphaltites. At the same time, hydropyrolysis is suitable for obtaining of activated carbon using asphaltites from Silopi deposit. Different oxygen groups were detected on the activated carbon surface, and their effect on surface properties of the samples was discussed.